Chemistry building - Unidentified photographer (Colorado State University. Libraries, 1969)
Blueprint Negatives of University Buildings (1881-1985): Box 2, 14-16 (Chemistry Building #150) 1969-1979.
Not digitized by CSUL Digital Services.
Keywords: chemistry; chemistry building